The impact of privacy and confidentiality laws on the conduct of clinical trials. - Armitage, J; Souhami, R; Friedman, L; Hilbrich, L; Holland, J; Muhlbaier, L; Shannon, J; Van Nie, A (2008)
Justifiable concerns about the use of personal data in many aspects of daily life have led to the recent introduction in many countries of laws intended to regulate data use. Although participation in randomized clinical trials is generally with informed consent, recruitment procedures, complete follow-up, and the efficient conduct of trials may be substantially affected by such national or local privacy legislation. The relevant laws often have exceptions that allow the use of patient information in the public interest - including the use of data collected to improve or monitor public health or as part of medical research. However, regulatory bodies often give conflicting interpretations of the law, and this affects the conduct of large-scale trials. In particular, unnecessarily restrictive interpretation of the law may be a serious impediment to identification of potential participants for a trial, access to records to confirm events, continued follow-up of patients after the trial has been concluded, and secondary use of the trial data for purposes not directly related to the original purpose of the study. These obstacles could be overcome by better informing patients of the uses of records for medical research purposes, by using informed consent procedures that explain the nature of the research and the uses of the data, and by the use of identifiers, such as social security numbers that allow central follow-up. The clinical trial research community needs to ensure that the substantial benefits of large-scale randomized trials are explained both to the public and to those responsible for introducing legislation. The negative impact of privacy legislation on the use of personal health information and on conducting large studies needs to be understood and minimized.